Inhibitors of human collagenase, MMP1 - De Andrade Leite, Sergio Roberto [UNESP] (Ecletica Quimica, 2009)
Different common drugs (Meloxicam, Tenoxicam and Piroxicam, and sodium alendronate) were tested both experimental and theoretically as inhibitors of interstitial human collagenase, also known as matrix metalloproteinase 1 (MMP-1). The in vitro collagenase activity, alone and in the presence of inhibitors, was quantified by the reaction with a fluorescent synthetic substrate and measuring the change of emission. Collagenase-inhibitor interaction was studied theoretically by computational calculations. Three among the four tested substances showed moderate inhibiting activity against the human collagenase.
Keywords: Collagenase; Docking; Human metalloproteinases; Inhibitors; MMP-1